Nuestra experiencia en el diagnóstico de la disección aórtica por tomografía multicortes. Our experience in the diagnosis of aortic dissection by multislice computed tomography. - Luis R. Llerena Rojas; Vladimir Mendoza Rodríguez; Eddy W. Olivares Aquiles; Yamilé Marcos Gutiérrez; Juan Valiente Mustelier; Lorenzo D. Llerena Rojas (ECIMED, 2011)
Introduction Aortic dissection (AD) is the most frequent and life-threatening acute aorticsyndrome. Currently the more used method for the aortic study is themultislice computed tomography. The purpose of this paper is to exposethe more relevant features in 22 patients with AD consecutively studiedby multislice computed tomography.Method All patients suspicious of AD studied during the last four years were includedand their main demographic, clinic and angiographic features weredescribed. Studies were performed by Somatom Cardiac Sensation, 64slices or Two Source Somatom Definition, Siemens Medical System, thecontrast medium used was Iopromide (Ultravist, Bayer Schering), Germany.Results Twenty (91%) patients were men. Mean age: 55 ± 9 years; minimum 24years and maximum 74. Type A AD was present in 15(68%) patients andtype B in 7(32%). Five (23%) patients had history of previous AD;20(91%) were hypertensive patients. Thoracic pain was the main symptomin 17(77%) patients. In 8 (36%) the coronary arteries were involved;20(91%) had at least dissection of one aortic branch. The mostfrequent re-entry site of the false lumen was the abdominal aorta belowthe renal arteries in 5 (23%). Patients with thromboses of the false lumen,rupture of the adventitial layer, mediastinal haematoma, hydrothoraxand circumferential intimal intussusception were observed.Conclusions The diagnoses of AD is made quickly and successfully by multislicecomputed tomography and in addition it is very useful for the assessmentof its angiographic features.